MONITORING FUNCTION OF DPRD TOWARD IMPLEMENTATION OF THE REGIONAL BUDGET REGULATION BULUNGAN REGENCY 2015 - Iskandar, Iskandar; Nasroen, Jimmy (Universitas Muhammadiyah Yogyakarta, 2018)
Based on the problem of research, the aim of this research are to determine and to asses deeply about monitoring function of Regional House of Representatives (DPRD) toward implementation of regional budget (APBD) regulation in Bulungan Regency in the year of 2015.The type of this research is descriptive-qualitative research which aimed to give a picture or painting of the situation systematically, factual, and accurate related with the research object then the result will be continued with detail explanation. Informan on this research are people who have competency to give information or data which are accurate and accountable related to the problem of research. The informan here are the whole members of Regional House of Representatives (DPRD) Bulungan Regency, that had been chosen randomly without consider their strata. The conclusion of this research said that the monitoring function toward regional budget (APBD) regulation in Bulungan regency had implemented but still not optimal. It is prove that there is a unsynchronized between planning with the result of local development planning consensus (Musrenbang) that was established and become the development priority. It is showed that political commitment of Regional House of Representatives (DPRD) toward budget monitoring still not yet optimal. The author give some suggestions to enforce the role of Regional House of Representatives (DPRD) in the field of monitoring. Regional House of Representatives (DPRD) should increase capability and knowledge, conceptional and operational institutionally aboutmonitoring function which tend to policy, Regional House of Representatives (DPRD) should hire experts which have capability in their fields, that do the assesment for give input.